(untitled) (Bangladesh Journal of Medical Science, 2021)
Background: Exclusive breast feeding is a simple, cost-effective and life-saving intervention for the health of an infant. Despite its undisputable benefits, in past two decades, exclusive breast feeding rates have not improved much globally. Among the South Asian countries, some are raising the bars and some are still struggling to meet the target for reaching sustainable development goal. So this review was planned to understand their situation and how to improve further for establishment of successful exclusive breast feeding. Main Body: On simple review of different literatures on exclusive breast feeding in South Asia, it was observed that the rate widely varies among the countries due to cultural and societal differences, women empowerment, illiteracy, maternal care practices, policy and program implementation and many other modifiable factors. Given the compelling evidence on the positive impacts of breast feeding, some integrated approaches are required involving policy makers, ensuring community participation and family centered counseling, providing health education for mothers and establishment of the Baby Friendly Hospital Initiatives. Conclusion: Experiences from successful neighboring countries can guide the other countries of South Asia to plan their roadmap. Moreover, further dissemination and scaling up of existing programs on exclusive breast feeding can help to achieve the desired target for Sustainable Development Goal. Bangladesh Journal of Medical Science Vol.20(4) 2021 p.725-731